Design technology of mosque mimbar Kedah Darul Aman / Ahmad Faisol Yusof ... [et al.] - Yusof, Ahmad Faisol; Yusof, Mohamad Zaki; Muhamad, Jamaludin; Abdul Rahim, Amran (2012)
Mosque is important as a sacred place for muslim especially to perform solat. In this research, the focus is on the aspect of 'mimbar'design which is an important element and only available in a mosque. Besides, Islam itself shows that Al-Quran and Prophet Muhammad (phub) sunnah are guidelines for muslims. But in term of the mimbar design, is there any specific guideline for their? The project has been carried out to identify mosque's mimbar typology.and it can be determined whether or not the mimbar adheres to syariah. The research is completed by applying a quantitative approach which requires huge database collection to get the best result. The research analyzes different aspects such as shape, size, location, entrance direction, entrance width, material use, colour, step and decoration of the mosque mimbar from twenty case studies around Alor Setar, Kedah.The methodology of the project research is a mix-method approach by using observation to the mosque mimbar and communicating with relevant authority, Mufti of Kedah. As a conclusion, results from this project can help designers and give information to people about mimbar designs.